Ring size matters: Supramolecular isomerism in self-assembled redox-active tetra- And hexaruthenium macrocycles - Fink, Daniel; Orth, Nicole; Linseis, Michael; Ivanovic-Burmazovic, Ivana; Winter, Rainer F. (Chemical Communications, 2020)
Self-assembly of a divinylthiophene-bridged diruthenium complex with 2,5-furandicarboxylate leads to the formation of two macrocyclic structures that differ solely with regard to their respective nuclearities. Both supramolecular isomers were fully characterized and the conversion of the hexa- to the tetraruthenium macrocycle was followed by NMR monitoring.
CRIS-Team Scopus Importer:2020-02-04